Pengaruh Capital Adequacy Ratio, Non Performing Loan, dan Rentabilitas terhadap Jumlah Pemberian Kredit (Studi Empiris Pada Perbankan yang Terdaftar di Bursa Efek Indonesia) - Suparno Suparno (Jurnal Telaah dan Riset Akuntansi, 2015)
This study purpose  to determine the influence of Capital Adequacy Ratio, Non-Performing Loans and profitability of the credit amount on the bank listed on the Indonesia Stock Exchange.This research is a research study population census which includes all banking companies as much as 18 banks. Data and information needed in this research are secondaryer data, obtained by means of data collection based on records that have been available in Indonesia Stock Exchange to classify financial data based on criteria that have been determined by multiple linear regression model.The results showed that the Capital Adequacy Ratio, Non-Performing Loans and profitability simultanously influence  the amount of credit at banks listed on the Indonesia Stock Exchange. While partially show that Capital Adequacy Ratio and indicates the direction of influence negatively on the amount of credit, Non-Performing Loans and showing the direction of impact negatively on the amount of lending and profitability impact and demonstrate a positive direction on the amount of credit at banks listed on the Indonesia Stock Exchange.KEYWORDS : Capital Adequacy Ratio, Non Performing Loan, Profitability and  amount of credit